Experimental study on the coupled shear flow behavior of jointed rock samples. (31st August 2018) - Shi, Z. M.; Shen, D. Y.; Zhang, Q. Z.; Peng, M.; Li, Q. D.
Abstract: Seepage within the rock mass mainly occurs along joints and depends on their morphology. Coupled shear flow tests were carried out on 9 jointed rock samples with different joint roughness coefficients (JRCs) and normal stresses, and on 27 samples with varying JRCs, normal stresses and seepage pressures. The results indicate that joint deformation switches from a sliding failure mode to a cutting failure mode with increasing roughness, while the joint is rather insensitive to normal stress and seepage pressure changes. Shear strength increases with decreasing seepage pressure and increasing JRC and normal stress. In all the tests, the hydraulic aperture at first decreased (due to shear contraction), then increased rapidly (because of shear dilation) and finally reached a stable value. The hydraulic aperture increased with decreasing normal stress but increasing JRC and seepage pressure. On the other hand, the shear strength was due mainly to cohesion and linearly changed with the seepage pressure. Based on the experimental results, an empirical equation was developed for obtaining the shear strength of jointed rocks experiencing a seepage pressure.